DAMPAK BULLYING TERHADAP KEPERCAYAAN DIRI ANAK - Nabilla Suci Darma Jelita; Iin Purnamasari; Moh. Aniq Khairul Basyar (Universitas Muria Kudus, 2021)
The purpose of this study was to analyze the impact of bullying on children's self-confidence at SD Negeri Kedungmundu Semarang.The research method used is a qualitative method approach with case studies. Data collection techniques used are interviews with perpetrators and victims of bullying, teachers and school principals. Observations were made to determine the impact of bullying behavior on children's confidence and to provide questionnaires to perpetrators and victims of bullying. Sources of research data are principals, teachers, and students involved in bullying cases, namely the perpetrators of bullying and victims of bullying. Techniques for the validity of the data in the research are technique triangulation and source analysis. Data analysis techniques used are data collection, data reduction, data display, conclusion/verification. The study was conducted on March 11, 2020 in the fourth grade of SD Negeri Kedungmundu Semarang.The results showed that the forms of bullying found in SD Negeri Kedungmundu Semarang were verbal bullying in the form of mocking, insulting physical deficiencies, calling parents' names. Non-verbal bullying in the form of kicking, hitting, pulling the veil, and fighting. Relational bullying in the form of exclusion and neglect. The impact of bullying behavior on self-confidence is that there are victims of bullying who experience a decrease in their level of confidence, but there are also victims of bullying who experience increased self-confidence because the bullying behavior becomes a motivation.